2000
DOI: 10.1348/014466600164462
|View full text |Cite
|
Sign up to set email alerts
|

Social identity and the true believer: Responses to threatened self‐stereotypes among the intrinsically religious

Abstract: That religion is an impactful social category has often been assumed but seldom tested. Based on social identity and self-categorization theories, it is argued that devout religious commitment reflects, at least in part, an individual's motivation to engage in religious self-stereotyping (i.e. to perceive oneself as an exemplary religious group member). In order to test this analysis, individuals scoring high or low on a measure of intrinsic religious orientation received false feedback that either threatened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 22 publications
3
48
0
Order By: Relevance
“…Previous work on religiosity and selfenhancement has often used a more sophisticated measure of religious orientation that distinguishes "intrinsic" religiosity from other orientations. Experimental work on religious selfstereotyping and similar mechanisms has specifically dealt with intrinsic religiosity (Burris & Jackson, 2000;Burris & Navara, 2002). We therefore expect similar findings for a measure of intrinsic religiosity.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous work on religiosity and selfenhancement has often used a more sophisticated measure of religious orientation that distinguishes "intrinsic" religiosity from other orientations. Experimental work on religious selfstereotyping and similar mechanisms has specifically dealt with intrinsic religiosity (Burris & Jackson, 2000;Burris & Navara, 2002). We therefore expect similar findings for a measure of intrinsic religiosity.…”
Section: Discussionsupporting
confidence: 57%
“…A plausible mechanism is that religious individuals are motivated to perceive themselves as exemplary religious group members (Burris & Jackson, 2000). This mechanism is here labeled religious self-stereotyping as it implies inferring judgments about oneself from the stereotype of the religious group to which one belongs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifi cally, for both Ghanaian Muslims and Christians as well as for Canadian Christians, religious fundamentalism was positively correlated with right-wing authoritarianism and positively associated with negative attitudes toward homosexuals (see also Hunsberger, 1996). In addition, Burris and Jackson (2000) have demonstrated that, for a sample of Christians, intrinsic religious orientation was strongly correlated with religious group identifi cation. Intrinsically religious participants, whose religious self-perceptions concerning religious group membership were threatened, showed increased religious self-stereotyping.…”
Section: Limitationsmentioning
confidence: 97%
“…Recent studies have successfully applied the self-categorization framework to religious groups. Burris and Jackson (2000) found that an intrinsic motivational orientation toward one's religious group predicted intensified commitment to the group in response to unfavorable feedback about how well one has met the group's behavioral standards. Applying this framework to well-being, strength of identification with the religious group has been found both to mediate some of the effects of social support on health (Krause & Wulff, 2005), and to mediate some of the effects of religious attendance on psychological well-being (Greenfield & Marks, 2007).…”
Section: A Group Processes View Of Religionmentioning
confidence: 99%